War and Peace - Tolstoy, Leo; Translated by Louise and Aylmer Maude (Ware Wordsworth Publishers, 1993)
War and Peace is a vast epic centred on Napoleon's war with Russia. While it expresses Tolstoy's view that history is an inexorable process which man cannot influence, he peoples his great novel with a cast of over five hundred characters.
Include Bibliography
Introduction and Notes by Henry and Olga Claridge
Keywords: Military campaigns -- Russia -- Napoleonic Wars (1800-1815)